Factor affecting economic growth in selected Southeast Asia countries / Nur Iyla Izzati Mohd Zaidi - Mohd Zaidi, Nur Iyla Izzati (Universiti Teknologi Mara Perlis, 2020)
The purpose of this research is to contribute to the finance literature by providing further evidence on the Factor Affecting Economic Growth in Selected Southeast Asia Countries. This research is novel given the fact that not many researchers have been done on selected richest Southeast Asia countries. In this study are investigate the relationship between selected macroeconomic and microeconomic variables including domestic credit (DC), net export (NETEXP), gross domestic product (GDP) and energy use (EGUSE) towards the economic growth in selected richest Southeast Asia country. This study used panel data where three (3) top three richest countries involved which is Singapore, Brunei and Malaysia within 10 years from 2007 to 2016. Fixed-effects (within) regression with cluster option had been selected as a final test in this study using STATA S.E 14.0. The finding of this study indicates that domestic credit (DC) and net export (NETEXP) is a significant positive relationship, energy use (EGUSE) is a significant negative relationship toward economic growth in Southeast Asia countries.